VERIFIKASI PENENTUAN ANGKA BAKTERI Escherichia coli PADA SAMPEL YANG DI-SPIKE MENGGUNAKAN METODE COLONY FORMING UNIT - Chairani Arizal; Aswal Harianto (LPPM UNIVERSITAS PERINTIS INDONESIA, 2019)
The water that must be drunk is healthy water that meets the requirements of Bacteriology, Chemistry, Radioactivity and Physicality based on Republic of Indonesia Minister of Health Regulation No: 492 / MENKES / PER / IV / 2010 concerning the requirements and supervision of clean water quality which includes physical requirements which are odorless, not colored and tasteless, where for the Coliform value is 0/100 mL. Escherichia coli is a fecal coliform bacterium and an indicator of the quality of drinking water because its presence in water indicates that the water is contaminated by feces. The aim of this study was to determine the value of accuracy, precision, detection limit, sensitivity and specificity of the calculated numbers of Escherichia coli bacteria from spike samples using the CFU method with agar chromocult media. The results of the bacterial results obtained on accuracy parameters were 229.33%, precision ie 26.35%, LOD which was 13.85 CFU / ml, LOQ ie 138.54 CFU / ml, and Specificity of 0%. Based on the results of verification of bacterial numbers obtained from the results of the accuracy test, precision that is not within the range of general requirements indicates that the method cannot be valid to use factors that affect high dilution, rapid bacterial growth rate, adequate nutrition and observer vision, whereas specificity indicate that chromocult coliform is very specific to Escherichia coli.